Inversion response to optimize lumped-element circuits for metamaterial - Uddin, Md Jasim; Ullah, Mohammad Habib; Latef, Tarik Abdul; Wan Mahadi, Wan Nor Liza (John Wiley & Sons, 2016)
Enhancing electromagnetic research on prior light bend mechanisms is a significant issue for composite material phenomena, and one that is not available in nature. The unit cell of metamaterial can be revised, such that it is significantly smaller than the free space of the wavelength. It is essential to extend the appropriate retrieval process to measure electrical and magnetic responses to the backward wave propagation and dispersion diagram characteristics. In this paper, we propose a retrieval process inversion response between known and unknown parameters of the lumped unit-cell circuits that optimizes the best fit parameters. By utilizing the optimization of particle swarm techniques, we provide appropriate values of periodic unit cells of CRLH transmission line circuits that matched with the microstrip implementation model. The group velocity of the wave is indicated in the parallel direction, whereas the phase velocity is in the anti-parallel direction. The dispersion diagram displayed a specifically left-handed and right-handed medium, and a tiny band gap appeared in the attenuation medium. The constitutive parameters of dielectric permittivity, permeability, and refractive index were obtained from the periodic composite transmission line circuits.